Empowering farmers through discovery learning: a case study of Farmer Field School (FFS) training on cocoa Integrated Pest Management (IPM) in Ondo State, Nigeria - Ajayi, M.T.; Banmeke, T.O.; Okafor, C. (2008)
The study assessed the effectiveness of Farmer Field School (FFS) training on farmers\' competence in Integrated Pest Management of cocoa and the transfer of knowledge to others in Ondo State, Nigeria. Using structured questionnaire and interview schedule, data from 60 randomly selected respondents made up of 30 trained FFS graduates (primary trainees) and 30 others trained by FFS graduates (secondary trainees) were used for the study. Findings show that a higher proportion of the respondents in both categories of trainees are males and a majority are married and belong to 31 –50 years age bracket. The result shows that about 63% of the primary trainees transferred the knowledge to others while the secondary trainees did not transfer the knowledge. Respondents from both categories of trainees found the FFS training to be more efficient than other trainings. FFS was found to improve the competence level of both categories of trainees especially on ability to conduct field studies and making observation themselves and also improve farmers\' confidence and reduction in agrochemicals use. However, the effectiveness of FFS was more pronounced in primary trainees than the secondary trainees. Respondents\' level of education (b = 2.765), number of years of cocoa farming (b=1.785) and participation in Farmer Field School training (b = 2.364) had significance influence on the respondents\' competence in cocoa IPM. For better efficiency, the inclusion of Farmer Field School training in agricultural extension programmes in addition to T&V system is recommended.